2021
DOI: 10.1002/aur.2615
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking autism spectrum disorder assessment for children during COVID‐19 and beyond

Abstract: The COVID-19 pandemic has posed unique challenges for families and caregivers, as well as for autism-focused clinicians, who are faced with providing a thorough and accurate evaluation of children's specific needs and diagnoses in the absence of inperson assessment tools. The shift to telehealth assessments has challenged clinicians to reconsider approaches and assumptions that underlie the diagnostic assessment process, and to adopt new ways of individualizing standard assessments according to family and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 64 publications
(77 reference statements)
0
28
0
2
Order By: Relevance
“…In addition, they also need to to prepare and send instructions and educational materials to parents prior to the virtual appointment. Parents, through parent training programs delivered by telematics systems, mediate intervention on their children [ 20 , 73 , 74 , 75 , 78 , 79 , 80 ], thus ensuring a more family-centred approach to care [ 81 , 82 ]. In contrast, few studies focus on distance interventions that directly target children and adolescents with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they also need to to prepare and send instructions and educational materials to parents prior to the virtual appointment. Parents, through parent training programs delivered by telematics systems, mediate intervention on their children [ 20 , 73 , 74 , 75 , 78 , 79 , 80 ], thus ensuring a more family-centred approach to care [ 81 , 82 ]. In contrast, few studies focus on distance interventions that directly target children and adolescents with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…There may also be factors related to the pandemic context that have exacerbated waiting times; for example, arising due to stay-at-home mandates, social distancing guidelines, staff redeployment and sickness, widespread disruptions to care pathways and difficulties experienced by people and their families with accessing telehealth ( 18 , 23 , 25 ). Nonetheless, only 58% of services in our study reported longer waiting times for assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Since the time our study was conducted, a limited number of studies [e.g., ( 21 24 )], and commentaries ( 19 , 25 ), have been published, focusing on autism assessment during the pandemic and outlining examples of adaptations to standard practice along with considerations for professionals. Yet overall, there is still much we do not know about how professionals are conducting autism assessments, which adaptations are more or less common (and considered more or less critical for reaching a diagnostic conclusion via telehealth), and whether this impacts on factors such as conversion rates and patient, family/carer and professional acceptability and satisfaction with service provision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations